Investigation on thermoelectric cooling system for battery pack of electrical vehicle - WENG Zhiqi; DENG Bin; ZHANG Xinwei; LI Guoneng*; GUO Wenwen; TANG Yuanjun; ZHENG Youqu (能源环境保护)
In order to promote the safety of the power battery pack in high-temperature environments for electrical vehicles, a thermoelectric cooling system was designed and tested. This system utilized a self-developed pin fin assisted cooling distributor, equipped with 6 thermoelectric cooling modules, and employed circulating cooling water for heat dissipation at the hot-ends. The coefficient of performance (COP) of the thermoelectric cooling system increased rapidly with the increase of the cooling air velocity and flow rate of cooling liquid, and then stabilized. The optimal cooling air velocity and flow rate of cooling liquid were 2.5 m/s and 33.3 mL/s, respectively. The maximum COP reached 0.26. For a lithium-ion power battery pack with a storage capacity of 36 kW·h, the temperature inside the battery pack case decreased by more than 20 ℃ under different heat generation rates (50~200 W). The initial temperature of the power battery pack dropped from 68 ℃ to below 45 ℃ at a heat generation rate of 200 W, indicating that the thermoelectric cooling system designed in this study could effectively reduce the temperature inside the power battery pack and improve the safety of electrical vehicle.